The privatization of environmental discourse: clean development and indigenous territoriality in western Panama - Jordan, Osvaldo (Abya-yala: Revista sobre Acesso à Justiça e Direitos nas Américas, 2018)
Facing the global ecological crisis, international organizations, national governments, financial institutions and private business have supported the idea of a green economy searching for win-win scenarios and public-private partnerships. Unfortunately, this perspective does not usually consider alternative conceptions of well-being, justice and happiness. The case of the Barro Blanco hydroelectric project in Western Panama warns against the underlying assumptions of the prevailing environmental discourse of sustainable development. Unless development projects start considering different opinions, ideals and expectations, there will be the possibility for protracted conflict and severe environmental damage as happened with the forceful flooding of Ngäbe communities in a hydroelectric reservoir linked with the Clean Development Mechanism (CDM) of the Kyoto Protocol. As negotiations continue for new market-based mechanisms to mitigate climate change, lessons should be learned from the Barro Blanco debacle to find new pathways that reduce greenhouse emissions and at the same time respect human rights and indigenous worldviews and territoriality.